2017
DOI: 10.1007/jhep12(2017)108
|View full text |Cite
|
Sign up to set email alerts
|

T -folds from Yang-Baxter deformations

Abstract: Yang-Baxter (YB) deformations of type IIB string theory have been well studied from the viewpoint of classical integrability. Most of the works, however, are focused upon the local structure of the deformed geometries and the global structure still remains unclear. In this work, we reveal a non-geometric aspect of YB-deformed backgrounds as Tfold by explicitly showing the associated O(D, D; Z) T -duality monodromy. In particular, the appearance of an extra vector field in the generalized supergravity equations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 125 publications
(277 reference statements)
8
71
0
Order By: Relevance
“…This then implies that the R-matrix is unimodular if and only if the Q-flux generated by the YB matrix is traceless, see (4.28). This is in agreement with the results of [39], which also finds that the non-unimodularity of the R-matrix is measured by the trace of the Q-flux. Looking at the expression (4.23), one sees that the trace of the Q-flux is just the divergence of Θ: Q IK I = ∂ I Θ IK , which is the non-commutativity parameter in the language of [42]- [44].…”
Section: The Dilaton Field and The Generalized Supergravity Equationssupporting
confidence: 93%
“…This then implies that the R-matrix is unimodular if and only if the Q-flux generated by the YB matrix is traceless, see (4.28). This is in agreement with the results of [39], which also finds that the non-unimodularity of the R-matrix is measured by the trace of the Q-flux. Looking at the expression (4.23), one sees that the trace of the Q-flux is just the divergence of Θ: Q IK I = ∂ I Θ IK , which is the non-commutativity parameter in the language of [42]- [44].…”
Section: The Dilaton Field and The Generalized Supergravity Equationssupporting
confidence: 93%
“…equations of motion [23,25,28]. However, as pointed out in [145,146], the dual geometry in fact satisfies the generalized supergravity equations of motion (GSE) [147,148]. When the target space satisfies the GSE, string theory has the scale invariance [147,149] and the κ-symmetry [148].…”
mentioning
confidence: 99%
“…To study models generated by I 1 and I 2 we decompose these matrices into product of special elements of NATD group. Namely, we note that I 1 can be written as I 1 = I A · I B where I A is given by (25) and I B is the B-shift (26). Similarly, I 2 can be decomposed as…”
Section: Poisson-lie Identities and Dualitiesmentioning
confidence: 99%
“…Long-lasting problem appearing in discussion of non-Abelian T-duality is that dualization with respect to non-semisimple group G leads to mixed gauge and gravitational anomaly, see [22], proportional to the trace of structure constants of g. Authors of paper [23] have found non-Abelian T-duals of Bianchi cosmologies [24] and have shown that instead of standard β-equations dual backgrounds satisfy the so-called Generalised Supergravity Equations containing Killing vector J whose components are given by the trace of structure constants. For Bianchi V cosmology this was observed already in [25]. Therefore, it is natural to ask if backgrounds and dilatons obtained from Bianchi cosmologies by Poisson-Lie identities and dualities satisfy Generalised Supergravity Equations as well and what Killing vectors have to be used.…”
Section: Introductionmentioning
confidence: 98%